Mental Health and Recovery Needs Among Women Substance Use Disorder Treatment Clients With Stalking Victimization Experiences - Logan, TK (Journal of drug issues, 2024)
This study examined mental health and recovery needs at substance use disorder (SUD) program entry and at follow-up (n = 2064) among: (1) women with no stalking victimization; (2) women with lifetime stalking victimization experiences; and (3) women with recent stalking victimization experiences (within 12 months of program entry). Stalking can be defined as a repeated pattern of behavior that creates fear or concern for safety or extreme emotional distress in the target. Women who experienced any stalking victimization, and particularly recent stalking victimization at program entry, had more recovery needs and increased mental health symptoms. At follow-up, women with any stalking victimization experiences continued to have more recovery needs with few differences between the lifetime and recent stalking victimization groups. Stalking victimization experiences were significantly associated with depression and anxiety symptoms in the multivariate analysis. Addressing stalking victimization during SUD treatment may be important to facilitate recovery.